A novel 111‐nucleotide duplication in the G gene of human metapneumovirus. (16th November 2017) - Saikusa, Miwako; Nao, Naganori; Kawakami, Chiharu; Usuku, Shuzo; Sasao, Tadayoshi; Toyozawa, Takahiro; Takeda, Makoto; Okubo, Ichiro
ABSTRACT: In 2017, novel human metapneumovirus (HMPV) A2b subgroup strains with a 111‐nucleotide duplication in the G gene was detected by the present team. These strains were related to previously identified HMPV A2b strains with a 180‐nucleotide duplication; however, they appeared to be different strains, produced by an independent duplication event. The recent evolution of HMPV suggests that careful monitoring of this virus is required.